A theological defence of Burkean conservatism and a critique of contractarian liberalism - Burgess, S (2015)
In this thesis I have provided a critique of the stream of contractarian liberalism which finds its source in the work of John Locke, tracing its influence through the French Revolution and into our own era in the work of the contemporary liberal theorist John Rawls. I have drawn particular attention to the substantive and methodological assumptions which unify these three instantiations of the contractarian tradition. I have challenged this stream of liberalism by offering an exposition of the thought of Edmund Burke. During the course of the thesis I have looked at the central themes which characterised Burke's thought, drawing particular attention to Burke's understanding of the British constitution, common law and his regard for the institutional church. Secondly, I have analysed the theological content of Burke's political thought, demonstrating that Burke's political thought emerged from his Christian faith and his concomitant belief in the natural law. I have argued that, as a result, there is a profound consonance between the central principles of the Christian faith and the conservative tradition which followed Burke. In the course of this argument I have defended the natural law school of Burkean scholarship and presented a clear link between Burke and the thought of Thomas Aquinas. Thirdly, I have unearthed some of the theological convictions which were historically resident in the British legal tradition that informed Burke's thought and I have shown how these assumptions run counter to the central ideas of the contractarian tradition. I have concluded by arguing that there are specifiable aspects of contractarian liberalism which should be treated with suspicion by Christians.